2003
DOI: 10.1111/j.1740-8261.2003.tb00468.x
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Analysis of 140 Dogs With Oral Melanoma Treated With External Beam Radiation

Abstract: Despite the early notion that canine oral malignant melanoma is radioresistant, recent data suggest that external beam radiotherapy is effective in local tumor control. However, optimal fractionation schedules have not been established. The high rate of regional and distant metastasis is another problem that has hindered long-term control. The role of chemotherapy in the management of canine oral melanoma has also not been determined. In this study, data from 140 dogs irradiated at North Carolina State Univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
188
0
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(201 citation statements)
references
References 33 publications
7
188
0
6
Order By: Relevance
“…A retrospective analysis of dogs with oral melanoma treated with external beam radiation showed that the median time to the first event was 150 days and the median survival was 210 days (n ¼ 140). 27 With an overall response rate of carboplatin (n ¼ 27) of 28%, the median duration of the objective response was 165 days. 28 When combined with platinum-based chemotherapy, hypofractionated radiation therapy yielded a better outcome with a median survival time of 363 days (n ¼ 39).…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective analysis of dogs with oral melanoma treated with external beam radiation showed that the median time to the first event was 150 days and the median survival was 210 days (n ¼ 140). 27 With an overall response rate of carboplatin (n ¼ 27) of 28%, the median duration of the objective response was 165 days. 28 When combined with platinum-based chemotherapy, hypofractionated radiation therapy yielded a better outcome with a median survival time of 363 days (n ¼ 39).…”
Section: Discussionmentioning
confidence: 99%
“…Survival times quoted for conventionally treated stage II or III oral CMM (Table 1.) range from 3-to 12 months with metastasis being a significant cause of mortality (Bateman et al, 1994;Freeman et al, 2003;MacEwen et al, 1986;Murphy et al, 2005;Proulx et al, 2003). It is, however, worth noting that not all oral CMMs are clinically aggressive and some early stage canine patients as well as patients with histologically benign lesions can have extended survivals (MacEwen et al, 1986;Smedley et al, 2011).…”
mentioning
confidence: 99%
“…Several reports have investigated the efficacy of CT in COMM, but there is no definitive evidence regarding its effectiveness (5,6,(7)(8)(9). Therefore, there is a need for an alternative treatment for COMM.…”
Section: Introductionmentioning
confidence: 99%
“…Melanoma treatment includes radiation therapy and chemotherapy (CT), either alone, as an adjuvant therapy following surgery, or in combination (2). Although radiation therapy provides effective local tumor control, it is only performed in selected facilities (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%